Utilization of Unmanned Aerial Vehicle (UAV) for Topographic Survey Using Ground Control Points (GCP) from Geodetic GNSS - Wirandha, Freddy Sapta; Ardiansyah, Ardiansyah; Nizamuddin, Nizamuddin (Graduate School of Universitas Syiah Kuala, 2023)
Mapping with UAVs is a large-scale mapping strategy or method that can shorten the implementation time compared to conventional survey methods that sometimes cannot represent an area as a whole. Aerial photos recorded by drones generally still have a level of position error of up to several meters, so tie points are needed to improve the accuracy of aerial photos. This research aims to utilize drone camera technology to produce geospatial data, both in the form of raster data from aerial photographs and vector data in the form of land contours showing the height of the land surface in Gampong Cot, Gampong Blang, Krueng Kalee, and Angan in Darussalam District, Gampong Durung and Neuheun in Masjid Raya District, Gampong Labuy and Lam Ujong in Baitussalam District. Aerial photo processing produces highresolution image data of 5 cm/pixel. Ground Control Points (GCPs) are used as tie points to improve the accuracy of aerial imagery. GCP measurements use geodetic GNSS, which has an accuracy of cm to mm. Aerial photos that previously had an error rate of 2-7 meters, after being bound with GCP points, the error rate decreased to below 1 meter. Aerial photographs also show that the land cover in the study area is partly forest. Some areas in the west and north are C excavation mining areas. Based on the contour extraction results, the ground elevation in block 1 (Gampong Durung, Gampong Cot, Gampong Angan, and Gampong Lam Ujong) is 66 to 301 meters, block 2 (Gampong Neuhen) is 50 to 260 meters, and block 3 (Gampong Lam Ujong and Labuy) is 90 to 188 meters.